A Pragmatic Study of Malwares to Enrich Application for Self Defence (International Journal of Engineering and Computer Science, 2014)
In the era of internet the probability of system or application being vulnerable to malwares such as viruses, Trojans, botnets etc. has provoked data corruption, data manipulation, security breaching and so on. Different techniques like antivirus and firewalls have emerged to combat against malware attacks. However existing signature based detections are unable to counteract anomalous behaviour of specific applications. There exist various behaviour based techniques which detects malicious content by observing applications at run-time. The focal point of this paper is on immunising an application against specific threats.